THE VIRTUAL SPACE OF POLICY AND FEATURES OF COMMUNICATION IN XXI CENTURY: SOCIAL AND PHILOSOPHICAL ANALYSIS - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the social and philosophical impact of the media on the formation of a virtual communication space policy.